Second trimester abortion as a cause of maternal death: a case report - Avcioglu, Sümeyra Nergiz (Pan Afr Med J, 2015)
Each year, an estimated 529 000 maternal deaths occur worldwide. In literature, it is known that maternal mortality can occur during pregnancy, peripartum and also in postpartum period. Although very rare, maternal deaths may occur after spontaneous abortion. In present case, 37 year old G5P4 (Caesarean Section) women was admitted to Adnan Menderes University, Obstetrics and Gynecology clinic with diagnosis of missed abortion at 18 weeks’ gestation. She had been hospitalized in the public maternity hospital for five days due to abortus incipience and prolapse of amnion membranes but had no contractions. Fetal heart beats ceased at the second day of hospitalization. Medically induced abortion was recommended but not accepted by the patient. At the fifth day of hospitalization, she was referred to our clinic due to deterioration of general health condition, low blood pressure and tachycardia. In emergency department, it was determined that she was not oriented, had confusion, had blood pressure of 49/25 mmHg and tachycardia. In ultrasonographic examination, 18 week in utero ex fetus was determined and there was free fluid in abdominopelvic cavity. The free fluid was suspected to be amniotic fluid due to rupture of uterus. Laparotomy was performed, no uterine rupture, hematoma or atony was observed. However during laparotomy, a very bad smelling odor, might be due to septicemia, was felt in the operation room. Cardiac arrest occurred during that operation. In autopsy report, it was concluded that maternal death was because of remaining of inutero ex fetus for a long time. In conclusion, although very rare, maternal deaths after spontaneous abortion may occur. Because spontaneous abortion is a common outcome of pregnancy, continued careful, strict monitoring and immediate treatment of especially second trimester spontaneous abortion is recommended to prevent related, disappointing, unexpected maternal deaths.